Climatology interdisciplinary data collection (CIDC) : monthly means of over 70 climate parameters for research and teaching - Kyle, H. Lee (NASA Goddard DAAC science data series., 1998)
Designed for study of global change, seasonal to interannual climate change, and other phenomena that require from one to dozens of interacting parameters. Also contains 3 heuristic scenarios dealing with monsoons, El Nino events, and global warming.